Managed as wild, horses influence grassland vegetation differently than domestic herds - Mutillod, Clémentine; Buisson, Elise; Tatin, Laurent; Mahy, Gregory; Dufrêne, Marc; Mesléard, François; Dutoit, Thierry (Biological conservation, 2024)
The urgent need to preserve ecosystems over vast areas has placed rewilding with wild herbivores to the forefront. However, there are still few scientific experimental field studies dealing with its effects on biodiversity and ecosystem services. Since 1993, in France, a socially natural population of wild horses (Equus ferus przewalskii) has been managed for its conservation. This introduction is an opportunity to compare this new management system with the multi-secular extensive sheep breeding and the more recent conventional domestic horse breeding. We sought to discover if plant communities show differences depending on the grazers and the managing system. We surveyed 208 plots divided into six grazed sites (two sites per type of grazer), where all plants species and their percent cover were listed within 1m2, and environmental variables – such as stones percent cover, slope - were measured within 100m2. To focus on the grazer effects, we used a subsample of plots with similar environmental variables. To study the grazing system - management choices - effects, we ran the analyses using all the plots. At both scales, our results show that species richness, evenness and heterogeneity are significantly higher with wild horses than with sheep grazing. Intermediate value is measured for evenness concerning domestic horses at the grazing system scale. Species richness is significantly higher for domestic horses than sheep focusing on the grazer; intermediate values are measured for evenness and heterogeneity. At both scales, wild horses also favour dicots rather than monocots. Our results indicate that grazing by horses maintains and promotes grassland diversity, especially when horses are managed ‘as wild’ - allowing them to express their natural behaviour. However, further studies are needed focusing on populations of patrimonial plant species over time, other taxonomical groups and/or on functional diversity and ecosystem services to compare and test more finely the effects of an animal bred extensively and ‘as wild’. [Display omitted] •Plant community responses vary depending on the grazer and on the management.•Horses induce higher species richness than sheep, wild horse higher evenness and heterogeneity.•Managing horses ‘as wild’ induces higher values for species richness, evenness and heterogeneity.•(Re)introducing ‘as wild’ horses promotes biodiversity, thus demonstrating rewilding benefits.•Further research is needed to better understand the effects of herd management.